PENGALAMAN MENGKONSUMSI BERITA ONLINE: PERSPEKTIF GENERASI MILENIAL DI JAWA TENGAH - Prinisia Nurul Ikasari; Lintang Citra Christiani (Universitas Teuku Umar, 2021)
Most of the people who access the internet are millennial generation, that is, the generation born between 1982 and 2000. Digitalization forces the mass media in Indonesia to participate in meeting the demands of society's need for up to date information. This study aims to examine the practices of the millennial generation in consuming online news. In particular, this study aims to reveal the diversity of meanings that arise from the experiences of audiences when consuming online news. This study applies a qualitative approach to the reception method. The comment column provides a reference space for itself to continue consuming the next news activity on the mass media or not. Comments can even be termed as a filter for news that millennial generation will consume. Storytelling as millennial generation's online news consuming experience. From the point of view of millennials storytelling helps facilitate their imagination through visual means.